2016
DOI: 10.3319/tao.2016.09.12.01
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Aftershocks in Taiwan: A Review

Abstract: We reviewed studies on aftershocks in Taiwan for the following topics: the spatial-temporal distributions and focal-plane solutions of aftershocks fromof thirty larger earthquakes with magnitudes > 5; the correlations between the mainshock and the largest aftershock based on dependence of the differences in magnitudes (∆M), occurrence times (∆T), epicenters (∆H), and focal depths (∆D) upon the mainshock magnitude, M m ; magnitude-dependence of p-value of Omori's law of aftershocks; the correlation between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…From the previous studies given above, there exists a clear relation between the characteristic aftershock parameters and structural properties of the aftershock region, since the region-time-magnitude variations of aftershock sequences include some useful information about the earthquake nucleation, fault geometry, the physical properties of the materials in the fault zone, distributions of slip, stress and temperature (Kisslinger, Jones 1991). There are many studies on the regional and temporal evaluation of aftershock sequences of mainshocks from Turkey and different parts of the world (e.g., Kisslinger, Jones 1991;Wiemer, Katsumata 1999;Enescu, Ito 2002;Bayrak, Öztürk 2004;Öztürk et al 2008;Wang et al 2016;Öztürk, Şahin 2019;Nanjo 2020;Öztürk 2021) and these researchers suggested that regional changes in b-value and p-value are controlled by rupture mechanisms during the mainshock, and the variations in these parameters are related to the material properties of the aftershock area. According to their results, the areas with a smaller b-value are related to the regions with a lower stress after the mainshock, and the regions with a higher p-value are related to the areas that the experienced higher coseismic slip distribution after the mainshock.…”
Section: Some Comments On the Regional Changes Of B-value And P-valuementioning
confidence: 99%
See 1 more Smart Citation
“…From the previous studies given above, there exists a clear relation between the characteristic aftershock parameters and structural properties of the aftershock region, since the region-time-magnitude variations of aftershock sequences include some useful information about the earthquake nucleation, fault geometry, the physical properties of the materials in the fault zone, distributions of slip, stress and temperature (Kisslinger, Jones 1991). There are many studies on the regional and temporal evaluation of aftershock sequences of mainshocks from Turkey and different parts of the world (e.g., Kisslinger, Jones 1991;Wiemer, Katsumata 1999;Enescu, Ito 2002;Bayrak, Öztürk 2004;Öztürk et al 2008;Wang et al 2016;Öztürk, Şahin 2019;Nanjo 2020;Öztürk 2021) and these researchers suggested that regional changes in b-value and p-value are controlled by rupture mechanisms during the mainshock, and the variations in these parameters are related to the material properties of the aftershock area. According to their results, the areas with a smaller b-value are related to the regions with a lower stress after the mainshock, and the regions with a higher p-value are related to the areas that the experienced higher coseismic slip distribution after the mainshock.…”
Section: Some Comments On the Regional Changes Of B-value And P-valuementioning
confidence: 99%
“…Thus, aftershock sequences continue to exist as the key features of earthquake activity, and hence in recent years an increasing attention has been given to the evaluation of aftershock sequences. Many statistical and physical models have been suggested to define the region-time-magnitude characteristics of aftershock occurrences, and a large number of analyses of the mainshock-aftershock pattern for different aftershock occurrences were achieved by different researchers (e.g., Utsu 1969;Wiemer, Katsumata 1999;Ogata 2001;Polat et al 2002;Bayrak, Öztürk 2004;Helmstetter, Shaw 2006;Öztürk et al 2008;Kayal et al 2012;Hainzl et al 2014;Adhikari et al 2015;Wang et al 2016;Özer, Polat 2017a, b;Wei-Jin, Jian 2017;Luginbuhl et al 2018;Öztürk, Şahin 2019;Nanjo 2020;Sedghizadeh, Shcherbakov 2022).…”
Section: Introductionmentioning
confidence: 99%